Penyusunan Balanced Scorecard pada PT Cipta Paramula Sejati (Jurnal Manajemen dan Organisasi, 2019)
PT Cipta Paramula Sejati is one of the companies engaged in the space and office rental business in Jakarta. PT Cipta Paramula Sejati manages the rental of office buildings and rooms in the Jakarta Design Center Building. Jakarta Design Center is a mall that has three types of businesses related to building space rental. Every company will be faced with various problems, both problems that come from within the company (internal) and problems from outside the company (external). This study aims to analyze the strategic objectives and key performance indicator (KPI) in terms of four perspective Balanced Scorecard (BSC), an also performance measurement methods at PT Cipta Paramula Sejati based on BSC concept. The analytical method used is the BSC. The study used a descriptive approach through in-depth interviews with respondents who were chosen intentionally (purposive sampling). The results of the study obtained twelve strategic targets and fourteen KPI. Based on the results of the BSC compilation of PT Cipta Paramula Sejati, the weighting for each BSC perspective was as follows: financial perspective of 27.78 percent, customer perspective of 27.78 percent, internal business process perspective of 25 percent, and learning and growth perspective of 19.44 percent.